Prevalence of preoperative anemia and transfusion practice in adult elective non-cardiac surgery: A prospective single centre 3 months audit / Vanessa Louis Lionel Louis - Vanessa Louis, Lionel Louis (2018)
Anemia is defined as a condition in which the red blood cells or the oxygen carrying capacity is insufficient to meet the physiological needs. According to WHO sex based criteria, anemia is diagnosed as less than 13 g/dl for men and less than 12 g/dl for women. We audited patients undergoing elective non cardiac surgeries in our hospital setting to see the prevalence of anemia, the timing of detection of anemia and the type of anemia. We also wanted to audit the incidence of transfusion preoperatively, intraoperatively and post operatively and the transfusion trigger. We also looked into the complications of blood transfusion and the morbidity and mortality including length of hospital stay, any death within hospitalization and the 30 day mortality. Elective procedures likely to be associated with high transfusion use were audited which included : gynaecological, colorectal, urological and arthroplasty surgeries.Our audit was a prospective single centre audit over the period of 3 months, from December 2017 up to mid March 2018 at the University Malaya Medical Centre, Kuala Lumpur and got a total of 306 patients. Patients that were included were all patients above the age of 18 in the following elective gynaecological, colorectal, urological and arthroplasty surgeries. Pregnant patients, any patients with American Society of Anaesthesiologists score 6 and all cancelled operations were excluded. Relevant data was extracted from the Hospital EMR (Electronic Medical Records). Data that was collected included patients characteristics and comorbiditites, type of operation and surgical discipline, selected laboratory investigations eg hemoglobin level, perioperative data for blood loss, blood transfusion, autologous iv techniques, post operative transfusion and complications of blood transfusion. We also measured the mortality and morbidity including length of hospital stay, death within hospitalization and the 30 days mortality as a secondary outcome for the audit. Our audit revealed that out of the 306 patients, according to the anemia definition of hb<13 for males and hb<12 for females, a total of 126 patients were anemic, 52 were males and 74 females. Out of the 126 anemic patients, 33.3% had their anemias detected only 1-6 days prior to surgery and none of the anemic patients had a complete blood profile to determine the type of anemia. As for the transfusion practice, 17 anemic patients received preoperative blood transfusion, 14 received intraoperative transfusion and 14 also received postoperative transfusion, and our study showed that persons who were anemic were more likely to receive blood transfusions. Morbidity and mortality of our study revealed that patients were anemia experienced more complications compared to those were not anemic, anemic patients were significantly associated with infections (p value: 0.0024) and cardiac complications (p value: 0.011) during their postoperative stay in the hospital. There was also significant difference in median for their length of stay in hospital between patients who were anemic (4 days) and patient who were not anemic (2 days).A larger population of patients should have been audited over a longer duration of time to determine a better incidence and prevalence of anemia, transfusion practices and morbidity and mortality in our centre. From our study, it shows that incidence and prevalence of anemia is significant in our population and they show a higher need for v blood transfusion. Also those anemic patients had more postoperative complications and longer hospital stays. It is important to note these findings so that we can work our way towards the formation of a patient blood management protocol for our centre